Performance of the combined hydropneumatic isolations on improving vibration of vibratory roller cab: Experiment and simulation. (April 2021) - Zhou, Huaxiang; Nguyen, Vanliem; Wu, Xiaoyan
This study, based on preeminent characteristics of both the pneumatic and hydraulic isolations, combined hydropneumatic isolations (CHPIs), is proposed for improving the cab ride quality of the vibratory rollers in low-frequency domain. A 3D dynamic model and mathematical model of the cab isolations and the vibratory rollers are established to simulate CHPI's characteristics under the excitations of the off-road terrain and vibratory drum at 28 Hz and 35 Hz. To enhance the reliability of research results, vehicle's mathematical models are also verified via the experimental investigation. The effectiveness of CHPIs on ameliorating the cab's ride quality is then analyzed via two indicators of the power spectral density (PSD) acceleration on the frequency region and root-mean-square (RMS) acceleration on the time domain of the cab and operator seat. It is found that with the combination of the high-elastic stiffness parameter and high nonlinear damping coefficient of CHPIs using for the vehicle's cab isolations, the results of the cab's ride quality are greatly improved compared with other cab isolations in the well-known existing works.